2022
DOI: 10.3390/diagnostics12040800
|View full text |Cite
|
Sign up to set email alerts
|

The ETS Homologous Factor (EHF) Represents a Useful Immunohistochemical Marker for Predicting Prostate Cancer Metastasis

Abstract: The main aim of this study was to investigate the risk of prostate cancer metastasis formation associated with the expression of ETS homologous factor (EHF) in a cohort of bioptic samples. To this end, the expression of EHF was evaluated in a cohort of 152 prostate biopsies including primary prostate cancers that developed metastatic lesions, primary prostate cancers that did not develop metastasis, and benign lesions. Data here reported EHF as a candidate immunohistochemical prognostic biomarker for prostate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…3D) 60,63 . Further, CBP was enriched for PCa-associated transcription factors, including ETS-factor, Elk4 and SP1 62,64,6770 . Conversely, in addition to FOXA1, p300 was enriched for mitochondrial factor (GFY), zinc finger proteins (Bc111a, ZNF143), and PCa- associated transcription factors (HOXB13) 71–78 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D) 60,63 . Further, CBP was enriched for PCa-associated transcription factors, including ETS-factor, Elk4 and SP1 62,64,6770 . Conversely, in addition to FOXA1, p300 was enriched for mitochondrial factor (GFY), zinc finger proteins (Bc111a, ZNF143), and PCa- associated transcription factors (HOXB13) 71–78 .…”
Section: Resultsmentioning
confidence: 99%
“…3D). Proximal to CBP binding, motifs are enriched for Ets-factors Elk4 and Sp1, which are linked to PCa oncogenic signaling 62,64,6770 . Intriguingly, proximal to p300 binding, motifs are enriched for GFY, ZNF143, and HOXB13, which are linked to mitochondrial signaling and zinc-finger function 71–78 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies highlight the implication of microRNAs (miRNAs) in cancer research, as they play an important role in regulating cancer cells and impacting various aspects of cancer progression, including apoptosis induction, cell cycle regulation, metastasis promotion, and angiogenesis stimulation [30,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. In a recent investigation by Xiong et al [79], the effects of circSETD3, a circular RNA containing multiple miRNA binding sites, were studied in CCA cells.…”
Section: Potential Therapeutical Approachesmentioning
confidence: 99%
“…The Gleason score (GS) is the most widely used tool to assess the aggressiveness of PCa [ 3 5 ]. Studies have reported that the number of positive needles of systematic biopsy is also one of the indicators for assessing PCa aggressiveness [ 6 ]. A considerable difference in prognosis exists between patients with ≥ 50% positive needles and those with < 50% positive needles [ 7 ].…”
Section: Introductionmentioning
confidence: 99%